Evidence of integrated health service delivery during COVID-19 in low and lower-middle-income countries: protocol for a scoping review. Issue 5 (3rd May 2021) - Neill, Rachel; Hasan, Md Zabir; Das, Priyanka; Venugopal, Vasuki; Jain, Nishant; Arora, Dinesh; Gupta, Shivam
Abstract : Introduction: The importance of integrated, people-centred health systems has been recognised as a central component of Universal Health Coverage. Integration has also been highlighted as a critical element for building resilient health systems that can withstand the shock of health emergencies. However, there is a dearth of research and systematic synthesis of evidence on the synergistic relationship between integrated health services and pandemic preparedness, response, and recovery in low-income and lower-middle-income countries (LMICs). Thus, the authors are organising a scoping review aiming to explore the application of integrated health service delivery approaches during the emerging COVID-19 pandemic in LMICs. Methods and analysis: This scoping review adheres to the six steps for scoping reviews from Arksey and O'Malley. Peer-reviewed scientific literature will be systematically assembled using a standardised and replicable search strategy from seven electronic databases, including PubMed, Embase, Scopus, Web of Science, CINAHL Plus, the WHO's Global Research Database on COVID-19 and LitCovid. Initially, the title and abstract of the collected literature, published in English from December 2019 to June 2020, will be screened for inclusion which will be followed by a full-text review by two independent reviewers. Data will be charted using a data extraction form and reported in narrative format with accompanying data matrix. Ethics and dissemination: No ethical approval is required for the review. The study will be conducted from June 2020 to May 2021. Results from this scoping review will provide a snapshot of the evidence currently being generated related to integrated health service delivery in response to the COVID-19 pandemic in LMICs. The findings will be developed into reports and a peer-reviewed article and will assist policy-makers in making pragmatic and evidence-based decisions for current and future pandemic responses.